Gene promoters are genomically encoded to facilitate histone exchange/incorporation. - Blaine Bartholomew (PLoS Biology)
Gene promoters are intrinsically hardwired not only to facilitate transcription preinitiation complex formation but also the release of paused RNA polymerase by H2A.Z. A new PLOS Biology study reveals poly (dA) tracts at promoters positively stimulate H2A.Z incorporation by the SWR complex in yeast.